Design of Smart Oligo(ethylene glycol)‐Based Biocompatible Hybrid Microgels Loaded with Magnetic Nanoparticles. Issue 1 (25th November 2014) - Boularas, Mohamed; Gombart, Emilie; Tranchant, Jean‐François; Billon, Laurent; Save, Maud
<x xml:space="preserve">Abstract</x> This article reports a rational strategy for preparing smart oligo(ethylene glycol)‐based hybrid microgels loaded with high content of homogeneously distributed preformed magnetic nanoparticles (NPs) (up to 33 wt%). The strategy is based on the synthesis of biocompatible multiresponsive microgels by precipitation copolymerization of di(ethylene glycol) methyl ether methacrylate, oligo(ethylene glycol) methyl ether methacrylate, methacrylic acid, and oligo(ethylene glycol)diacrylate. An aqueous dispersion of preformed magnetic NPs is straightforwardly loaded into the microgels. Robust monodisperse thermoresponsive magnetic microgels are produced, exhibiting a constant value of the volume phase transition temperature whatever the NPs content. The homogeneous microstructure of the initial stimuli‐responsive biocompatible microgels plays a crucial role for the design of unique well‐defined ethylene glycol‐based thermoresponsive hybrid microgels. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>